Sense of order: the effects of machine aesthetic on biomaterials favourability - Bahrudin, Fadzli Irwan; Liew, Yong Kian; Zakariya, Khalilah; Daud, Nuraini; DongMyung, Park (Aalborg University, Denmark, 2025)
Designers are increasingly creating materials from renewable and recycled sources to support a circular economy, aiming to mitigate the adverse effects of linear production and consumption. These materials are considered sustainable alternatives to non-renewable materials, such as fossil fuel-based plastics. While users may be drawn to the sustainability narrative and "biography" of such materials, the highly natural appearance of biomaterials can sometimes evoke unappealing user responses. This study examines how "machine aesthetics"—visible signs of production like graphical embossment and engraving—impact user perceptions of biomaterials. The research explores how surface alterations influence emotional responses and underlying appraisals by comparing reactions to biomaterial samples with a high degree of naturalness against those with embossed and engraved surfaces. Findings reveal that machine aesthetics evoke a sense of order, contributing to favourable responses and minimising other negative evaluations of the material aspects. Although users value biomaterials for their natural origins, structured human-imposed aesthetics satisfy a desire for aesthetic coherence and control. This finding suggests that people appreciate sustainable materials' natural imperfections when presented within a framework of manageability and familiarity.